Diagnóstico do processo de desenvolvimento de produto de uma empresa da indústria de autopeças - Ghiralde, Rafael (Universidade Federal de São Carlos, 2025)
The improvement of performance of the Product Development Process (PDP) in an industrial landscape is imperative to comply with the requirements for innovation, quality, and reduced timelines. This dissertation assesses the PDP of a company in the auto parts sector with a diagnostic tool developed from a systematic literature review (SLR) and application of action research method. The analysis of 615 documents indexed in the Scopus database in a SLR evidence a gap in the literature regarding methods for assessing the PDP. We identified only two studies aligned with the research objective, alongside emerging topic trends such as sustainability, risk management, and Industry 4.0. Due to the absence of comprehensive diagnostic approaches for the PDP, we used the reference model by Rozenfeld et al. (2006) as the foundation for developing an instrument in the empirical phase. The research team comprised the author and eight professionals from the studied company. The assessment tool developed during the action research consists of 47 questions, structured according to the macro-stages of the PDP and incorporating specific aspects of the company’s PDP process. The results show not only the proposition of an adaptable tool for assessing PDPs but also the identification of critical factors impacting process performance within the organization, such as deficiencies in resource allocation, interdepartmental communication, and the application of risk management tools. These findings enable the proposal of corrective actions, underscoring the study’s contribution to continuous process improvement in dynamic industrial contexts.
Diagnosis of the product development process of a company in the autoparts industry
Keywords: Gestão do processo de desenvolvimento de produto na indústria automotiva; Desenvolvimento de produto; Diagnóstico do processo de desenvolvimento de produto; Product development management in automotive industry; Product development; Diagnosis in the process of product development; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::GERENCIA DO PROJETO E DO PRODUTO